Spiders - Gibbons, Gail. (New York : Scholastic, 1993)
Examines the physical characteristics, behavior, habitats, and different kinds of spiders.
Mode of access: Internet.
Keywords: Spiders -- Juvenile literature; Spiders -- Juvenile literature